Antioxidant activity of two varieties of Ocimum basilicum L. for potential use in phytocosmetics (2016)
This investigation aimed to evaluate two varieties of Ocimum basilicum L., known as Basil, as potential raw material for the cosmetic industry, assessing their antioxidant properties, considering their industrial use in phytocosmetics. The antioxidant activity of essential oils (EOs) for the species Ocimum basilicum var. cinammom and var. album, were obtained by distillation steam using a Clevenger-type device. The antioxidant capacity was evaluated by the method of bleaching radical 1,1-diphenyl-2-picryl hydrazyl (DPPH) and the method of linoleic acid peroxidation (ferric thiocyanate). The EOs of the two species had significant antioxidant properties. The method of DPPH facilitated the evaluation of the antioxidant capacity versus the concentration of EOs, showing an efficient concentration at 10 ppm. On the other hand, the ferric thiocyanate method displayed an efficient inhibition up to 360 h (15 d). The obtained results demonstrated the antioxidant capacity of EOs in the investigation. The capacity was related to their chemical composition (phenylpropane and oxygenated monoterpenes). Therefore, EOs can be considered as a potential source in the field of phytocosmetics.